Construction and valuation of a systematization instrument within nursing assistance to teenagers in hospitals - Daniela Karina Marques; Maria Miriam Nóbrega (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
Introduction: The adolescence is a period of time in the process of development of a human being, it is not only marked for the chronological age of a person, as well as for changes in the biological, psychological and socio-culturals processes which constitute the individual particularity and peculiarities of social groups in a society. The lack of professional knowledge on the characteristics about adolescence, to offer those patients cares in nursing, makes the correct attendance difficult to their necessities, this generates a lack of information to their family, professionals and the proper teenager. To contribute with those related questions, the nurse launches the hand using the systematization assistance of nursing that is a space to express and get the necessities, collaborating to solve problems of nurse competence and articulations with other sectors, professionals or support structures. In this present study, it was opted by the utilization of the human basic Horta theory of necessities, which is one of the most well known in Brazil, it is a theory that fits to attend the clients chosen, and it is also the theoretical referential of the project of systematization of nursing assistance of the University hospital Lauro Wanderley. Objective: to build and valuate an instrument to systematization of nursing assistance, though the identification of the empiric indicators of human basic necessities in teenagers at hospitals. Methodology: This study is a methodological research that was applied at the Children section in Lauro wanderley Hospital, João Pessoa city - P.B - Brazil. We had as population and sample the assistant nurses and professors that work inside the Children Clinic, beyond the term of free and clarified assent, they accepted to participate of this study. It was developed 3 phases: Identification of empiric factors of human basic necessities in adolescents treated in hospitals; development of affirmative diagnosis, and nursing interventions, from the clinical pointers of the humans basic identified necessities and also validated; formatting and valuation of an instrument to the systematization assistance of nursing, having all the nursing process. Results: we made an ample review of the literature to identify the teenagers' necessities having as a base what was proposed by the Horta theory, we got specifics indicators for teenagers which were validated by assistant nurses and professors. It was developed affirmatives of diagnosis/results and interventions of nursing that were soon after used to build the instrument to valuable. After this validation that was elaborated by the final version of the instrument, we considered its relevance for the practice care. Final Considerations: We hope that the construction of the instrument of systematization within the nurse assistance for teenagers (treated in hospitals) can promote the development of new researches, to favor the nursing teaching and facilitate the communication and register of nursing assistance, to transform it more effective and to promote visibility of the assistance to clients and other professionals of the health team in the hospital.